Winckelmann e sua inserção no ambiente das artes em Roma - Avolese, Claudia Valladao de Mattos (Figura: Studies on the Classical Tradition, 2019)
The present article discusses Winckelann’s relations to the artistic environment in Rome during in mid-Eighteenth Century. Although most of the scholarly work on Winckelmann focusses on his aesthetic theory, he was also a centralfigure of the Roman art world, interacting lively with many renowned artists of the time, such as Anton Raphael Mengs, Charles-Louis Clérisseau, Gavin Hamilton, Johannes Wiedewelt, among many others. The present article intends to examine some of these interactions considering it as animportantfactor,both in the development of Winckelmann’s writings after he arrived in Italy, and in the foundation of a neoclassical idealthat would spread throughout Europe in the last decades of the 18th Century.